Short-term efficacy of non-pharmacological interventions for global population with elevated blood pressure: A network meta-analysis - Shao, Taihang; Liang, Leyi; Zhou, Chengchao; Tang, Yaqian; Gao, Wenqing; Tu, Yusi; Yin, Yue; Malone, Daniel C.; Tang, Wenxi (Frontiers in Public Health, 2023)
Background This study aims to compare the potential short-term effects of non-pharmacological interventions (NPIs) on prehypertensive people, and provide evidence for intervention models with potential in future community-based management. Methods In this Bayesian network meta-analysis, Pubmed, Embase, and Web of science were screened up to 16 October 2021. Prehypertensive patients (systolic blood pressure, SBP 120–139 mmHg/diastolic blood pressure, DBP 80–89 mmHg) with a follow-up period longer than 4 weeks were targeted. Sixteen NPIs were identified during the scope review and categorized into five groups. Reduction in SBP and DBP was selected as outcome variables and the effect sizes were compared using consistency models among interventions and intervention groups. Grade approach was used to assess the certainty of evidence. Results Thirty-nine studies with 8,279 participants were included. For SBP, strengthen exercises were the most advantageous intervention group when compared with usual care (mean difference = −6.02 mmHg, 95% CI −8.16 to −3.87), and combination exercise, isometric exercise, and aerobic exercise were the three most effective specific interventions. For DBP, relaxation was the most advantageous intervention group when compared with usual care (mean difference = −4.99 mmHg, 95% CI −7.03 to −2.96), and acupuncture, meditation, and combination exercise were the three most effective specific interventions. No inconsistency was found between indirect and direct evidence. However, heterogeneity was detected in some studies. Conclusion NPIs can bring short-term BP reduction benefits for prehypertensive patients, especially exercise and relaxation. NPIs could potentially be included in community-based disease management for prehypertensive population once long-term real-world effectiveness and cost-effectiveness are proven. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=151518, identifier: CRD42020151518.